Rationale and protocol for the 7- And 8-year longitudinal assessments of eye health in a cohort of young adults in the Raine Study - Lee, S.S.Y.; Lingham, G.; Yazar, S.; Sanfilippo, P.G.; Charng, J.; Chen, F.K.; Hewitt, A.W.; Ng, F.; Hammond, C.; Straker, Leon; Eastwood, Peter; MacGregor, S.; et al. (BMJ PUBLISHING GROUP, 2020)
Introduction Eye diseases and visual impairment more commonly affect elderly adults, thus, the majority of ophthalmic cohort studies have focused on older adults. Cohort studies on the ocular health of younger adults, on the other hand, have been few. The Raine Study is a longitudinal study that has been following a cohort since their birth in 1989-1991. As part of the 20-year follow-up of the Raine Study, participants underwent a comprehensive eye examination. As part of the 27- and 28-year follow-ups, eye assessments are being conducted and the data collected will be compared with those of the 20-year follow-up. This will provide an estimate of population incidence and updated prevalence of ocular conditions such as myopia and keratoconus, as well as longitudinal change in ocular parameters in young Australian adults. Additionally, the data will allow exploration of the environmental, health and genetic factors underlying inter-subject differential long-term ocular changes.